PENERAPAN METODE DISTRIBUTIF DALAM MENENTUKAN JUMLAH BAGIAN HARTA BERSAMA - Basaruddin Basaruddin (JURNAL AKTA YUDISIA, 2021)
Common property is property a type of property which is obtained by a married couple during their marriage. When a divorce happe, the formerly married couple filled a lowsurt in order to obtain or split one property they once belong. The court usually divide the cuealth base on the regulation namely 50/50, this decision usually trigred dissatisfaction of one party because the decision was deem unfair. The distribution method appars as alternative method to solving problem by revieuming of how much the contributied from formerly married couple during their marriage.This thesis focuses on whether “distributive justice” is able to be solve the problem by determining the number of common property divition. With the distributive method, it is possible to determine the share of the ex-husband and ex wife based on the contribution made during the household. This distributive method determines the share of each property that is owned proportionally. The justice to be realized in this method is to give same rights to ex-husbands or exwives according to the portion or distribution made when building a household.This thesis illustrates that distributive justice is one of solution/alternative that is able to answer the problem of determination the number of common property divitions both formerly married couple by prioritizing the fair divition and professionally.